A phase 2 and biomarker study of cabozantinib in patients with advanced cholangiocarcinoma. Issue 11 (13th February 2017) - Goyal, Lipika; Zheng, Hui; Yurgelun, Matthew B.; Abrams, Thomas A.; Allen, Jill N.; Cleary, James M.; Knowles, Michelle; Regan, Eileen; Reardon, Amanda; Khachatryan, Anna; Jain, Rakesh K.; Nardi, Valentina; et al.
Abstract : BACKGROUND: Advanced cholangiocarcinoma carries a poor prognosis, and no standard treatment exists beyond first‐line gemcitabine/platinum‐based chemotherapy. A single‐arm, phase 2 and biomarker study of cabozantinib, a multikinase inhibitor with potent activity against vascular endothelial growth factor receptor 2 (VEGFR2) and MET, was performed for patients with advanced refractory cholangiocarcinoma. METHODS: Previously treated patients with unresectable or metastatic cholangiocarcinoma received cabozantinib (60 mg orally and daily on a continuous schedule). The primary endpoint was progression‐free survival (PFS). Tumor MET expression and plasma biomarkers were evaluated. RESULTS: The study enrolled 19 patients with cholangiocarcinoma (female, 68%; median age, 67 years; intrahepatic vs extrahepatic, 84% vs 16%). The median PFS was 1.8 months (95% confidence interval, 1.6‐5.4 months), and the median overall survival (OS) was 5.2 months (95% confidence interval, 2.7‐10.5 months). Grade 3/4 adverse events occurred in 89% of the patients and included neutropenia (5%), hyperbilirubinemia (5%), epistaxis (5%), bowel perforation (5%), enterocutaneous fistulas (5%), and hypertension (11%). One patient with 3 + MET expression in the tumor stayed on treatment for 278 days, but the MET expression did not correlate with the outcomes in the overall study population. Plasma vascular endothelial growth factor, placental growth factor, and stromal cell–derived factor 1α increased and soluble VEGFR2 and angiopoietin 2 decreased after treatment (all P values < .01). Plasma tissue inhibitor of matrix metalloproteinase 1 was inversely correlated with PFS, and soluble MET (sMET) and interleukin 6 were inversely correlated with OS. CONCLUSIONS: In unselected patients with cholangiocarcinoma, cabozantinib demonstrated limited activity and significant toxicity. In the first clinical trial to assess the role of MET inhibition in cholangiocarcinoma, 1 patient with a MET‐high tumor had a prolonged benefit from treatment. Baseline plasma soluble MET was associated with OS. Any further development of this drug in cholangiocarcinoma should include a dose reduction and a biomarker‐driven approach. Cancer 2017;123:1979–1988 . © 2017 American Cancer Society . Abstract : In a phase 2 trial in patients with advanced refractory cholangiocarcinoma, cabozantinib has demonstrated limited efficacy and significant toxicity. A biomarker analysis shows on‐target antiangiogenic activity of cabozantinib, and baseline plasma‐soluble MET correlates with overall survival. Any further development of this drug in cholangiocarcinoma should include dose reduction, a biomarker‐driven approach, and the consideration of its combination with other drugs.